The relationship between transmission misinformation, COVID-19 stress and satisfaction with life among adults - Nguyen, Phuong Thi Hang; Van Huynh, Son; Nguyen, Nhi Ngoc Yen; Le, Tran Bao; Le, Pha Cam; Nantachai, Gallayaporn; Tran-Chi, Vinh-Long (Frontiers in Psychology, 2023)
The perplexing evolution of the COVID-19 pandemic has had a significant effect on the spiritual lives of Vietnamese people in general, and particularly adults. The objective of this study was to ascertain the link between adult satisfaction with life and COVID-19 stress in Vietnam and investigate if COVID-19 transmission disinformation modifies the effect of COVID-19 stress on adult satisfaction with life. A total of 435 Vietnamese adults were enrolled online to finish answering, including the Satisfaction with Life Scale (SL), the COVID-19 Stress Scale (CS), and the COVID-19 Transmission Misinformation Scale (CTMS), consisting of 350 females and 85 males. Correlation, regression, and basic mediation analyses were used to dissociate the data. According to the findings of our study, there is a difference in gender in satisfaction with life. Females have a greater degree of satisfaction with life than males. Significant differences exist between relatives of direct and indirect COVID-19 transmission misinformation workers. People who had relatives who were frontline medical staff had higher COVID-19 Transmission Misinformation than others. There is a positive correlation between satisfaction with life and COVID-19 spreading disinformation, but it can have adverse effects on persons’ physical health. Additionally, COVID-19 transmission misinformation has a role in the relationship between COVID-19 stress and adult life satisfaction. Individuals are more likely to access misinformation about COVID-19 transmission, which results in enhanced life satisfaction. During the COVID-19 epidemic, adults in Vietnam should be aware of the damaging consequences of COVID-19 transmission misinformation on their stress levels. Stress may significantly influence not just one’s mental health but also other aspects of one’s life. Clinicians should be aware of COVID-19 transmission misinformation and stress, which affect psychological treatment.